Molecular Epidimiology of Hepatitis C Genotype of UKMMC - N.A Mohamed; Z. Zainol Rashid; K.K. Wong; S.A Abdullah (Universiti Putra Malaysia, 2024)
7TH NATIONAL INFECTIOUS DISEASE SEMINAR AND WORKSHOP- THE PANDORA BOX OF THE VIRAL INFECTIONS UPM, SERDANG. 6TH – 8TH NOVEMBER 2012